Analysis of Students' Ability to Understand Mathematical Concepts After Learning to Use Learning Media on Circle Material in Class IX SMP Negeri 1 Kisaran T.P 2023/2024 - Lumban Batu, Widayu T.; Syafitri, Ely; Sirait, Lusi (Holistic Science, 2024)
This research aims to describe students' ability to understand mathematical concepts for each indicator so that it is known which indicators students experience problems with. This research also aims to determine the level of ability of students based on ability level categories. The method used in this research is descriptive qualitative. The instrument used in this research was a question/test of the ability to understand mathematical concepts, consisting of 4 validated questions. This research was carried out in class IX-11 of SMP Negeri 1 Kisaran which was carried out in the odd semester of the 2023/2024 academic year. Only 50% of students were able to fulfill the indicators of restating concepts, 77% of students were able to fulfill the indicators of classifying and grouping objects according to certain properties in accordance with their concepts, 56% of students who were able to fulfill the indicators were developing the concepts they already had, and 17% of students were able to meet the indicators of using and utilizing and choosing certain procedures or operations and applying them to problem solving. Furthermore, the research results showed that the level of understanding of mathematical concepts in the high category was 4 people or 13.33%, the level of understanding of mathematical concepts in the medium category was 22 people or 74.33%, and the level of understanding of mathematical concepts in the high category was 4 people or 13.33%. Researchers can conclude that students are still experiencing problems in the first and third indicators because 50% of students have not yet reached these indicators.